Identifying value in healthcare transformation initiatives: an evaluation of an approach to benefits realisation - Dionne Matthew; Venessa Vas; Mark Smith; Linda Eftychiou; Loretta Gyambibi; Hassan Al-Omari; James Glass (BMJ Open Quality, 2023)
Benefits realisation management (BRM) aims to facilitate the process of identifying, measuring and tracking desired benefits derived from a project. Improvement methodology frameworks often describe BRM as integral to identifying and measuring value derived from transformation initiatives within the National Health Service and beyond. Despite this, reporting of benefits realisation plans and methodological approaches to identifying and measuring benefits remains surprisingly scarce.This project aimed to pilot and evaluate the application of a purpose-designed benefits mapping template with seven newly funded transformation projects across three hospitals in the UK. The scope of the template was to identify key project benefits and metrics associated with the project initiatives. Plan-do-study-act (PDSA) cycles were used to capture the approach and utilisation of the template by project teams. These methods also enabled critical review of the template as an enabler to identifying relevant benefits and project metrics.Stakeholder engagement with the templates was variable. This was attributed to clinical pressures induced by the second wave of COVID-19 in the UK. Despite this, teams were able to produce completed templates outlining a number of wide-ranging benefits. Themes of benefits drawn from the maps include patient experience, patient outcomes, staff experience, access to care and efficiency. Qualitative feedback from teams included the reported value of a structured template to help recognise all the potential benefits associated with each project initiative. The PDSA cycles highlighted the template as an early step in BRM. Further components to this process are recommended to include consensus of the key metrics to be measured, a tool that summarises the reporting details of those metrics, and an effective means to collate reported metrics overtime.